On The Expected Values of Distribution of the Sample Range of Order Statistics from the Geometric Distribution - Calik, Sinan; Colak, Cemil; Turan, Ayse (Wayne State Univ Press, 2009)
The expected values of the distribution of the sample range of order statistics from the geometric distribution are presented. For n up to 10, algebraic expressions for the expected values are obtained. Using the algebraic expressions, expected values based on the p and n values can be easily computed.
Keywords: Order statistics; expected value; moment; sample range; geometric distribution